Quality of life of post-stroke patients - Bártlová Sylva; Šedová Lenka; Havierniková Lucie; Hudáčková Andrea; Dolák František; Sadílek Petr (Sciendo, 2022)
Stroke is a disease whose consequences have a considerable impact on the quality of the patient's life. It is a widespread disease that has a disabling impact on life and, in addition to physical changes, brings about a number of psychological and cognitive processes.